Numerical studies on elastic properties of graphene sheets and free vibration of carbon nanotubes by atomistic simulation and equivalent continuum modelling - Damodara Reddy Chilla (2008)
The present research deals with determination of elastic properties of finite graphene sheets and CNTs by equivalent continuum modelling, and free vibration analysis of plain as well as fluid conveying CNTs by atomistic modelling of stiffness and mass properties.